Application of AI on cholangiocarcinoma - Huang, Jianhao; Bai, Xuesong; Qiu, Yanyu; He, Xiaodong (Frontiers in Oncology, 2024)
Cholangiocarcinoma, classified as intrahepatic, perihilar and extrahepatic, is considered as a deadly malignancy of hepatobiliary system. Most of cholangiocarcinoma are asymptomatic. Therefore, early detection of the cholangiocarcinoma is significant but still challenging. Routine screening of tumor lacks specificity and accuracy. With the application of AI, high-risk patients can be easily found by analyzing the clinical characteristic, serum biomarkers and medical images. Besides, AI can be used to predict the prognosis including recurrence risk and metastasis. Although it has some limitations, AI algorithms will still significantly improve many aspects of cholangiocarcinoma in the medical fields with the development of computing power and technology.